FORMATISASI ONTOLOGI MANAJEMEN DAKWAH - ., Fahriansyah (UIN Antasari Banjarmasin, 2017)
When viewed in terms of elements of dawah combined with the ontology of general management, the study area of dawah management as a whole is 80 format. And when viewed in terms of the combination of dawah interaction with the ontology of general management, then obtained 96 formulation format, so that the total format of ontology of dawah management is 176 formulations ontology format.